Puerilities : Erotic Epigrams of The Greek Anthology - Hine, Daryl (Book collections on Project MUSE., 2001)
"Elegiac lyrics celebrating the love of boys, which the translator terms Puerilities, constitute most of the twelfth book of The Greek Anthology. That book, the so-called Musa Puerilis, is translated in this, the first complete verse version in English. It is an eroticopia of short poems by great and lesser-known Greek poets, spanning hundreds of years, from ancient times to the late Christian era." "The epigrams - wry, wistful, light-hearted, libidinous, and sometimes bawdy - revel in the beauty and fickle affection of boys and young men and in the fleeting joys older men find in loving them. Some, doubtless bandied about in the lax and refined setting of banquets, are translated as limericks. Also included are a few fine and often funny poems about girls and women."--Jacket.